How do you factor #21x^3 - 18x^2 + 7x - 6# by grouping?

2 Answers
Jun 29, 2016

Answer:

Expression#=3x^2(7x-6)+1(7x-6)=(7x-6)(3x^2+1).#

Explanation:

Observe that #3x^2# can be taken out as common from the first two terms, 7, from the last two terms, only #1# can be taken out. Hence,

Expression#=3x^2(7x-6)+1(7x-6)=(7x-6)(3x^2+1).#

Jun 29, 2016

Answer:

#(7x-6)(3x^2+1)#

Explanation:

Group the terms in 'pairs' as follows.

#[21x^3-18x^2]+[7x-6]#

now factorise each 'pair'.

#color(red)(3x^2)(7x-6)color(red)(+1)(7x-6)#

We now have a common factor of (7x -6) in each pair which we can take out.

#(7x-6)(color(red)(3x^2+1))#

#rArr21x^3-18x^2+7x-6=(7x-6)(3x^2+1)#